Task-based language teaching (TBLT) approach in learning Arabic language: students’ voice - Hashim, Marzidah; Selamat, Nita Fauzee; Raja Sulaiman, Raja Munirah (International Journal of Science Commerce and Humanities, 2014)
Task-Based Language Teaching (TBLT) is a new approach in teaching second language particularly in Arabic language. The approach, which employs student-centred approach, is viewed as more effective than the traditional way. This approach is slowly gaining its popularity among Arabic language educators and learners all around the world. In Malaysia, the Centre for Languages and Pre-University Academic Development (CELPAD) of International Islamic University Malaysia is one of the first institutions of education to implement this new way in teaching Arabic language. As such, this study was conducted in order to explore the students’ opinion towards the implementation of task-based language teaching (TBLT) in this learning institution. 10 respondents were randomly selected from the students in Arabic elementary level studying at Centre for Foundation Studies, International Islamic University (CFSIIUM). A semi structured interview was carried out on them. The qualitative results via nvivo analysis were used to examine students’ view towards the implementation of task-based language teaching (TBLT) in Arabic language. The findings unveil that while the respondents were positive and motivated to learn Arabic language using this approach, they also disclosed some challenges that they face.